Layer-by-Layer modification of graphite felt with MWCNT for vanadium redox flow battery. (1st August 2019) - Etienne, Mathieu; Vivo-Vilches, Jose F.; Vakulko, Ivan; Genois, Claire; Liu, Liang; Perdicakis, Michel; Hempelmann, Rolf; Walcarius, Alain
Abstract: Layer-by-Layer (LbL) deposition of multi-walled carbon nanotubes (MWCNT) was used to modify porous electrodes for vanadium redox flow batteries. Preliminary studies performed over glassy carbon (GC) electrodes showed that assemblies obtained with MWCNT displayed better mechanical stability than those prepared with other carbon nanoforms. The LbL process involved successive deposition of the polyethylenimine (PEI) and carbon nanotubes dispersed with poly(acrylic acid) (PAA). The thickness of the MWCNT assembly deposited onto a GC strongly influenced the electrochemistry of VO2 + /VO 2+ species. The thicker the film, the better the electrochemical reversibility resulted. An apparent electron transfer rate constant k app of 5 × 10 −4 cm s −1 was determined for a glassy carbon electrode modified with one hundred bi-layers and treated at 650 °C in inert atmosphere. The LbL technique was applied to the modification of graphite felt (GF) electrodes. GF electrodes modified with ten bilayers of PEI-PAA(MWCNT) were tested in a vanadium redox flow battery, showing a net decrease in the charge and discharge overpotentials with respect to the unmodified graphite felt. Lower overpotentials for charge-discharge resulted in higher energy and voltage efficiencies for the battery with modified GF electrodes. Furthermore, cyclability of the system was tested and no fading was observed in the battery performance after one hundred cycles.